2013
DOI: 10.1002/ccd.25006
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter trans‐apical closure of paravalvular mitral and aortic leaks using a new device: First in man experience

Abstract: This report describes the first use of a new paravalvular leak (PVL) device designed specifically to close paravalvular mitral and paravalvular aortic leaks. The first patient had severe paravalvular mitral leak that was closed using the transapical route with a rectangular designed PVL device that has an oval waist for self-centering and the second patient had moderate paravalvular aortic leak that was closed with a square designed device that has a round waist for self-centering. Both patients had complete c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Recently, Goktekin et al introduced a new device which is specifically designed for PVL closure. This device was used in two patients with 100% procedural and clinical success . The authors indicated the need for further trials before the widespread dissemination and use of this device.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Goktekin et al introduced a new device which is specifically designed for PVL closure. This device was used in two patients with 100% procedural and clinical success . The authors indicated the need for further trials before the widespread dissemination and use of this device.…”
Section: Introductionmentioning
confidence: 99%
“…A trans-apical approach is also feasible, with the benefit of allowing direct entry of the mitral PVL regardless of its location; this can be performed percutaneously or open [2]. Disadvantages to a percutaneous apical approach are that it is more invasive and requires additional pre-procedure planning and imaging (i.e., ultrasound, echocardiography, and/ or computed tomography) and that there is limited availability of dedicated apical closure devices domestically or internationally [5][6][7]. The open approach has additional limitations, such as an increased risk of apical tear, bleeding, myocardial damage, arrhythmia, coronary damage, and infection.…”
Section: Discussionmentioning
confidence: 99%
“…The Amplatzer Vascular Plug (AVP) II is widely used in the USA while in Europe the most frequently used device is the AVP III. At this time, the only device specifically approved to TPVL closure by the European Commission is the Occlutech PLD [25].
Fig.
…”
Section: Transcatheter Techniques For Tpvl Closurementioning
confidence: 99%